1995
DOI: 10.1007/bf00511231
|View full text |Cite
|
Sign up to set email alerts
|

Physical conditioning in rats influences the central and peripheral catecholamine responses to sustained exercise

Abstract: We have investigated the effect of treadmill running in rats (25m.min-1 using a 3% gradient; for 1 h or 2 h) on the cortical extracellular concentrations of noradrenaline (NA) and its main metabolites-3,4-dihydroxyphenylglycol and 3-methoxy-4-hydroxyphenylglycol- and the plasma adrenaline (A) and NA concentrations in relation to prior physical conditioning (1 or 2-h running.day-1 for 12 days). Cortical microdialysates and peripheral blood were collected during 1-h resting, 1-h or 2-h running and for 1 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…Also, the treadmill running stimulated concomitantly peripheral catecholamines secretion and central noradrenergic activity, i.e. NA turnover and release (Pagliari and Peyrin 1995). In this study, we observed that CSITR provoked a decreased morning CORT concentration in the plasma.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 60%
“…Also, the treadmill running stimulated concomitantly peripheral catecholamines secretion and central noradrenergic activity, i.e. NA turnover and release (Pagliari and Peyrin 1995). In this study, we observed that CSITR provoked a decreased morning CORT concentration in the plasma.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 60%
“…Increased extraneuronal metabolism of norepinephrine (NE) has been observed, as have increased levels of NE and its metabolites in the frontal cortex and hippocampus [8,9]. NE turnover and release also are shown to be increased during exercise [10,11]. Similarly, increased serotonin synthesis, metabolism [12], and release [13][14][15] also have been observed.…”
Section: Neurobiological Effects Of Exercise and Their Relationship Tmentioning
confidence: 90%
“…Physical exercise influences the brain through many processes, including some that apparently promote neuron survival. Changes in the synthesis and metabolism of neurotransmitters (Dey et al, 1992;Meeusen and Meirleir, 1995;Pagliari and Peyrin, 1995), and classical neurotrophic factors (Neeper et al, 1995(Neeper et al, , 1996, following physical exercise have been reported. In addition to the traditionally defined neurotrophic factors, a diverse set of factors have been reported to have growth-promoting effects in the central nervous system.…”
Section: Discussionmentioning
confidence: 98%
“…Local actions include 1) increased neuronal (synaptic) activity (Vissing et al, 1996) and blood flow (Jørgensen et al, 1992) in a number of brain regions; 2) changes in the synthesis and the metabolism of neurotransmitters (Dey et al, 1992;Meeusen and Meirleir, 1995;Pagliari and Peyrin, 1995), neurotrophic factors (Neeper et al, 1995(Neeper et al, , 1996, and antioxidant enzymes (So-mani and Husain, 1996); and 3) local structural changes, such as increased capillary density (Isaacks et al, 1992). Any of the above-mentioned factors might affect the normal aging of the brain according to the holistic network theory of aging, in which the entire orchestrated process of multiple endogenous and exogenous damaging and protective agents and processes are assumed to determine the capability of the system to preserve homeostasis (Kowald and Kirkwood, 1994).…”
mentioning
confidence: 99%